2020
DOI: 10.1186/s13071-020-04069-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen depletion and subsequent radioprotective effects during irradiation of mosquito pupae in water

Abstract: Background: Radiation induced sterility is the basis of the Sterile Insect Technique, by which a target insect pest population is suppressed by releasing artificially reared sterile males of the pest species in overflooding numbers over a target site. In order for the sterile males to be of high biological quality, effective standard irradiation protocols are required. Following studies investigating the effects of mosquito pupae irradiation in water versus in air, there is a need to investigate the oxy-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 54 publications
(60 reference statements)
2
25
0
Order By: Relevance
“…Our study also showed that hypoxia protects from O 2 effects during adult irradiation as was seen in mosquito pupae ( Yamada et al, 2019 , 2020 ), but may come with its own negative effects. Anoxia had high radioprotective effects, with up to a 14-fold increase in residual fertility compared to males irradiated with the same dose in normoxia.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Our study also showed that hypoxia protects from O 2 effects during adult irradiation as was seen in mosquito pupae ( Yamada et al, 2019 , 2020 ), but may come with its own negative effects. Anoxia had high radioprotective effects, with up to a 14-fold increase in residual fertility compared to males irradiated with the same dose in normoxia.…”
Section: Discussionsupporting
confidence: 69%
“…For mass irradiation at the pupal stage, the pupae would need to be placed in sufficient water within the irradiation canister to provide buoyancy to avoid the pupae at the bottom being crushed. However, this creates a hypoxic environment as pupae submerged in water continue to respirate through their cuticle and quickly deplete the surrounding water of dissolved oxygen ( Yamada et al, 2020 ). As hypoxia reduces irradiation effects, the irradiation of pupae in water results in differential levels of sterility within the sample ( Yamada et al, 2020 ), therefore this method for irradiation cannot be reliable unless, again, the full cohort is significantly overdosed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors that affect dose–response in mosquito species currently targeted by the SIT (namely Anopheles arabiensis, Aedes aegypti, and Ae. albopictus ) have been investigated at the Insect Pest Control Laboratory IPCL of the Joint FAO/IAEA Centre of Nuclear Techniques in Food and Agriculture, such as handling methods, life stage, pupal age, strain origin, ambient temperature, and atmosphere during irradiation 18 , 19 . However, additional factors that affect dose response are suspected and require further scrutiny.…”
Section: Introductionmentioning
confidence: 99%